The relationship between intellectual curiosity and adolescents’ mathematical problem-solving ability: A moderated mediation model - Yongzhao Wang; Lijun Zhou; Bingqing Xie; Lisha Wang; Hua Jin (PLoS ONE, 2026)
The ability to solve mathematical problems is one of the key skills for students to excel in mathematics. Based on PISA 2022 data from Ireland (N = 5,521), the current study constructed a moderated mediation model to systematically examine how intellectual curiosity (IC) influences mathematical problem-solving ability (MPSA) through the mediation of self-efficacy (SE), and to test the moderating role of perseverance (PE). The results indicated significant positive correlations among IC, SE, PE, and MPSA. Further mediation analysis revealed that IC not only exerted a direct effect on MPSA, but also affected MPSA indirectly through the role of SE, accounting for 45.40% of the total effect. Moreover, the moderated mediation analysis uncovered a dual role of PE in the mechanism through which IC influences MPSA: it negatively moderated the paths from IC to SE and from IC to MPSA, while positively moderating the path from SE to MPSA. Multi-group analysis revealed significant heterogeneity in the mechanism across gender and economic, social, and cultural status (ESCS). Specifically, male students relied more heavily on the mediating path of SE, whereas female students exhibited a stronger direct effect of IC. Students with low ESCS primarily depended on the direct drive of IC, whereas their high-ESCS counterparts achieved ability enhancement more through the mediating pathway of SE. These findings elucidate the cross-group psychological mechanisms influencing MPSA, validate the applicability of self-determination theory and social cognitive theory in standardized educational contexts, provide empirical evidence for Ireland to formulate differentiated and targeted mathematics education intervention policies, and offer practical insights for promoting the comprehensive development of adolescents.